2015
DOI: 10.3109/13651501.2015.1050401
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between temperament, character and the autistic trait in parents of children with autistic spectrum disorder

Abstract: Our findings suggest that self-directedness may be an autistic trait.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…To more accurately classify a patients' disturbed functioning as either ASD or PD or as both in clinical practice, further multidisciplinary longitudinal research is needed to better understand the different developmental pathways and natures of ASD, temperament, character, and PDs. Distinct personality domains have already been shown in ASD parents, suggesting specific personality features inherited as autistic phenotypes (Kadak et al 2015).…”
Section: Future Directionsmentioning
confidence: 91%
See 1 more Smart Citation
“…To more accurately classify a patients' disturbed functioning as either ASD or PD or as both in clinical practice, further multidisciplinary longitudinal research is needed to better understand the different developmental pathways and natures of ASD, temperament, character, and PDs. Distinct personality domains have already been shown in ASD parents, suggesting specific personality features inherited as autistic phenotypes (Kadak et al 2015).…”
Section: Future Directionsmentioning
confidence: 91%
“…Studies were excluded for four reasons: first, studies with adult participants not diagnosed with ASD (Austin 2005;Bejerot et al 2001;Butler et al 2015;Eryigit-Madzwamuse et al 2014;Hurst et al 2007;Kadak et al 2015;Kunihira et al 2006;Mealy et al 2014;Picardi et al 2015;Pisula et al 2015;Wakabayashi et al 2006); second, studies that examined autistic traits in participants with PDs not diagnosed with ASD (Rydén et al 2008); third, studies that targeted temperament and character aspects in children and adolescents with ASD (Barger et al 2014;Barneveld et al 2011;De Pauw et al 2011;Kerekes et al 2013;Schwartz et al 2009); and finally, a study with adults with ASD already included in an earlier study by the same author (Sizoo et al 2015) was excluded as it did not yield additional data.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Autism Spectrum Quotient is a questionnaire used in order to reveal ASD symptoms in clinical or nonclinical populations. In several studies, it was shown to reveal BAP (55,70,71). Even though broad ASD phenotype is determined in mothers and fathers of children with ASD, a study on children with OCD has not been conducted up to present day.…”
Section: Discussionmentioning
confidence: 99%